The moderating effect of education, experience and distributive justice on the relationship between psychological empowerment and employee performance in Ar-Rahn Sdn. Bhd. - Siti Mashita Marijin (2019)
The key objective of this research is to study the relationship between psychological empowerment and employees’ performance in Ar-Rahn Sdn. Bhd., one of a micro financing companies and is also known as an Islamic pawn broking system in Malaysia. In order to achieve the objective career in performance, the theory of empowerment and social exchange theory have been applied for this study. This cross-sectional study proposed a model which looks into the relationship between four dimensions of psychological empowerment (meaning, competence, self-determination and impact) and employees’ performance. This thesis also investigates the role of demographic variables which are educational level and years of experience, and distributive justice as the moderators between psychological empowerment and employees’ performance. The questionnaires were completed by 162 employees of Ar-Rahn Sdn. Bhd. from 30 branches in Malaysia, and the data was analyzed using SPSS Version 22.0. The results demonstrate that psychological empowerment is positively related to the task performance of employees in Ar-Rahn Sdn. Bhd. The results also show that distributive justice positively and significantly affects employees’ performance. However, both demographic variables do not have any significant influence on employees’ performance. This study highlights the importance of enhancing psychological empowerment to promote employee performance especially to achieve their objectives and targets.